Controls of carbon and nitrogen releases during crops' residue decomposition in the Red River Valley, USA. Issue 5 (15th April 2020) - Chatterjee, Amitava; Acharya, Umesh
ABSTRACT: Decomposition of crop residue releases nutrients and preserves soil organic matter dynamics. The decomposition rates of six crop residues namely, corn ( Zea mays ), dry bean ( Phaseolus vulgaris ), soybean ( Glycine max ), potato ( Solanum tuberosum ), sugarbeet ( Beta vulgaris ) and spring wheat ( Triticum aestivum ), were studied at three field-sites: Casselton, North Dakota, USA, and Ada and Downer of Minnesota, USA. Litterbags were placed on soil surface on 31 October 2016, and subset was retrieved after 6 months (8 April 2017) and finally after a year (30 October 2017). Crop residue type had significant effect on remaining mass%, carbon (C) and nitrogen (N) release, and C:N ratio. After 1 year, remaining mass% followed the sequence of corn (82%) > soybean (74%) > wheat (72%) > dry bean (55%) > potato (40%) > sugarbeet (17%). Among sites, Ada had higher remaining biomass C and N than Downer but similar to Casselton. Sugarbeet and corn had the highest (0.0054 d −1 ) and the lowest (0.0005 d −1 ) decomposition rate, respectively. Decomposition rate had a close relationship with initial residue C:N ratio. Conversion to intensive corn–soybean rotation might increase the residue load on the surface and reduce C and N mineralization loss.